PO12 Chemical characterization, antiplasmodial activity against P. falciparum (W2) and cytotoxicity of the ethanolic extract and fractions of Curarea toxicofera (Wedd.) Barneby & Krukoff - Hernández Carvajal, Jorge Enrique; Alves, Maria Fernanda; de Oliveira, Alaíde Braga; Brandão, Geraldo Célio; Hata , Yoshie Adriana; Garavito C, Giovanny; Luengas C, Pilar Ester (Revista Productos Naturales, 2025)
Malaria is a parasitic disease present in the tropics. According to the world malaria report of 2023, an estimated of 249 million cases and 11.7 million deaths were reported worldwide in 2022 [1]. Curarea toxicofera (Menispermaceae) is a native neotropical plant, traditionally used in the treatment of malaria by the Hitoma community in Amazonas-Colombia. In a previous study, this plant showed a promising in vitro antiplasmodial activity (IC50 = 8 ± 3.9 μg/mL) [2]. Therefore, it was chosen to continue its chemical and biological characterization.
Keywords: Bisbenzylisoquinoline alkaloids; menispermaceae; antiplasmodial activity; cytotoxicity